A case report of successful ex utero intrapartum to resection of a fetal pericardial teratoma: understanding variables affecting management - Patange, Amit; Kumra, Elina; Derderian, Sarkis; Jaggers, James; Londono-Obregon, Camila; Pettersen, Michael (Prenatal Cardiology, 2024)
Fetal pericardial teratomas are rare cardiac tumours that are known to grow rapidly, accumulate pericardial effusions, and in some cases cause fetal hydrops and demise. We report a case of successful fetal resection of such a tumour using an ex utero intrapartum treatment (EXIT) to resection strategy in which management was complicated by an anteriorly positioned placenta. A 29-year-old primigravida was diagnosed at 21 weeks of gestation with a large fetal intrapericardial teratoma and a large pericardial effusion. A pericardiocentesis was performed at 24 weeks’ gestation. The tumour continued to grow rapidly. An anteriorly positioned placental would have made early fetal resection technically challenging. She was closely followed with weekly fetal cardiac monitoring for evolving hydrops utilising fetal cardiac output, amongst other parameters. At 33 weeks’ gestation, the tumour was resected using an EXIT to resection strategy. Early fetal resection has been advocated for rapidly growing pericardial teratomas because the likelihood of survival drops once hydrops develops. However, in some instances early resection may be difficult, as in our patient who had an anterior placenta. In this report we highlight the strategies used in monitoring this mass with the goal of maximising gestation age at the time of resection. This was achieved by using a combination of an initial therapeutic fetal pericardial tap followed by an eventual EXIT to resection. This strategy can be particularly beneficial in selected patients in whom early fetal resection may be challenging or possibly even contraindicated for various reasons.